Proliferação celular em gestações naturais e de conceptos bovinos transgênicos e clonados, que expressam a proteína fluorescente verde (GFP) - Oliveira, Fernanda Paes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
For the placental growth and fetal nutrition, high rates of growth and differentiation are necessary for a proper balance between proliferation and cell death of placental cells. These cells have specific properties in relation to its metabolic, endocrine and angiogenic function and they are fundamental to the development of the fetus throughout pregnancy. In this study, the occurrence of cell proliferation was assessed in placentomes by cloned transgenic bovine conceptuses (n=5) and by artificial insemination (AI), in the 60 and 90 days of gestation, and they development were interrupted and recovering the pregnant uterus. The samples were cut and fixed in paraformaldehyde 4% aqueous solution in sodium phosphate buffer (PBS) 0.1M at pH 7.4, for verification of the morphology and performing immunohistochemistry. The results were compared with bovine cloned and AI. The reults obtained were compared between transgenic cloned bovine conceptuses and AI. In all groups and gestational periods, the fetal epithelium presents positive labeling to cell proliferation. In 60 days gestation the positive labeling of the manipulated gestations was less evident in relation to the natural gestations. On the other hand, in 90 days gestation the immunoreactivity of the placentomes of the cloned conceptuses was more intense, not just in the epithelium, but also in the fetal connective tissue, fact not observed in the natural gestation, were the positive reaction was less evident in the fetal connective tissue. In this study was noted a possible imbalance in the patterns of the cell proliferation in the transgenic cloned bovine conceptuses, because in the early gestation (60 days) they presented a lesser proliferative activity, and in the 90 days a increase, may be this fact one of the factors leading to placental abnormalities. Therefore, the results of verification of cell proliferation and understanding are important for the understanding of possible fails...

Para o crescimento placentário e a nutrição fetal, altas taxas de crescimento e diferenciação celular são necessárias para um balanço adequado entre proliferação e morte celular das células placentárias. Estas células possuem propriedades específicas em relação a suas funções metabólicas, endócrinas e angiogênicas, sendo fundamentais para o desenvolvimento do concepto ao longo da prenhez. Neste estudo, foi avaliada a ocorrência de proliferação celular em placentônios provenientes de conceptos bovinos transgênicos clonados (n=5) e de inseminação artificial (IA) (n=18), nos períodos de 60 e 90 dias de gestação, que tiveram seu desenvolvimento interrompido e houve a recuperação do útero gestante. As amostras de placentônio foram recortadas e fixadas em solução aquosa de paraformoldeído a 4% em tampão fosfato de sódio (PBS) a 0,1M pH 7.4, para verificação da morfologia, e realização da técnica de imuno-histoquímica. Os resultados obtidos foram comparados entre bovinos clonados transgênicos e de IA. Em todos os grupos e períodos gestacionais, o epitélio fetal apresentou marcação positiva para proliferação celular. Aos 60 dias a marcação positiva no epitélio uterino das gestações manipuladas foi pouco evidente em relação às de gestações naturais. Por sua vez aos 90 dias a imunorreatividade dos placentônios dos conceptos clonados, foi muito intensa não só no epitélio, mas também no tecido conjuntivo fetal, fato não observado na gestação natural, onde a reação positiva foi pouco evidente no tecido conjuntivo fetal. Neste estudo foi demonstrado um possível desequilíbrio nos padrões de proliferação celular nos conceptos bovinos clonados transgênicos, pois no início da gestação (60 dias) apresentaram menor atividade proliferativa e aos 90 dias um aumento, podendo ser este fato um dos fatores que levam às anormalidades placentárias. Desse modo os resultados da verificação..
Keywords: Genetica animal; Clonagem; Animais transgênicos; Placenta; Animal genetics